Adult Cutaneous Rhabdomyosarcoma (RMS) - Vathana Ketheeswaranathan; Michael Monteiro; Allan Ah-Weng (Elsevier, 2022)
Rhabdomyosarcoma is a malignant soft tissue tumour with a skeletal muscle differentiation. Adult RMS is rare and develops more commonly over the extremity followed by head and neck region. It is extremely rare for a RMS to present as a primary cutaneous tumour. A cutaneous metastasis is also a possibility, although this is a very unusual occurrence.